Kendala dan Dampak Pelaksanaan Pajak Restoran Berdasarkan Qanun Kota Banda Aceh Nomor 7 Tahun 2011 Terhadap Pendapat Asli Daerah di Kota Banda Aceh - Althaaf, Muhammad Athaya; Huseno, Tun; Ardieansyah, Ardieansyah (Innovative: Journal Of Social Science Research, 2025)
This study discusses the implementation of Restaurant Tax in Banda Aceh based on Qanun of Banda Aceh City No. 7 of 2011, as well as the obstacles and its impact on the Local Revenue (PAD). The main focus of this research is on how the restaurant tax collection mechanism is carried out according to the applicable regulations, and the challenges encountered in its implementation. The aim of this research is to explain how well the restaurant tax is implemented in Banda Aceh according to the existing rules, and to identify problems that arise in the tax collection process. This study employs a qualitative method with a literature study approach, gathering information from various sources such as books, articles, and other relevant writings. The findings reveal that, although restaurant taxes play a significant role in increasing PAD, there are still challenges such as a lack of understanding among restaurant business owners regarding their tax obligations and an inefficient reporting system. Some of the problems identified include low awareness of restaurant owners about the importance of tax obligations and the inability of some small business owners to comply with tax regulations correctly. Therefore, it is recommended that the government be more proactive in providing socialization and support to restaurant owners, as well as improving the tax payment and reporting systems to make them easier and more transparent. This research is expected to contribute to the local government in enhancing the efficiency of restaurant tax collection, as well as strengthening public participation in regional development through more optimal tax contribution.